Integration Of Islamic Social Finance And Green Finance In Improving The Economic Resilience Of Halal Msmes - Agus Rohmat Hidayat; Feri Hardiyanto; Rudi Ferdiansah (Journal of Management Economic and Financial, 2026)
This study examines the integration of Islamic Social Finance (ISF) and Green Finance (GF) in strengthening the economic resilience of Halal MSMEs in Kuningan Regency, West Java. Using a quantitative approach with Ordinary Least Squares (OLS) multiple regression and Sobel mediation test on 120 sample respondents, the findings show that ISF (B = 0.384; P< 0.001), GF (B= 0.291; p < 0.001), their interaction terms ISF×GF (B = 0.178; P= 0.006), and Halal Business Index (B = 0.214; p < 0.001) significantly and positively affects economic resilience. The model explains 72.14% variance (R² = 0.7214). Furthermore, the Halal Business Index partially mediates the relationship between ISF, GF, and economic resilience (Sobel z > 3.0; P < 0.01). These results confirm that synergistic integration of ISF and GF, underpinned by halal principles and productive social financing (zakat, infaq, waqf), substantially enhances the economic resilience and sustainability of Halal MSMEs.